2022
DOI: 10.1055/s-0042-1757629
|View full text |Cite
|
Sign up to set email alerts
|

Direct Carotid-Cavernous Fistula Caused by Internal Carotid Artery Perforation by a Microcatheter Body during Mechanical Thrombectomy

Abstract: Rapid advances in emergent mechanical thrombectomy have resulted in a higher occurrence of arterial perforations during neurointerventions. Here, we report a case of internal carotid artery (ICA) perforation during mechanical thrombectomy in a 78-year-old man with a left middle cerebral artery occlusion. The ICA was perforated by a microcatheter during thrombectomy, forming a direct carotid-cavernous fistula. A two-stage drainer occlusion was conducted because of cortical venous reflex aggravation and ocular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This was probably caused by pull-out vessel injury of the meningohypophyseal trunk branching from the cavernous segment of the ICA. The study of Miyamoto et al [ 3 ] reported that direct CCF is caused by ICA perforation by a microcatheter body during MT. Our case report suggests that the tortuosity of the ICA could be a potential predisposing factor for iatrogenic CCF[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably caused by pull-out vessel injury of the meningohypophyseal trunk branching from the cavernous segment of the ICA. The study of Miyamoto et al [ 3 ] reported that direct CCF is caused by ICA perforation by a microcatheter body during MT. Our case report suggests that the tortuosity of the ICA could be a potential predisposing factor for iatrogenic CCF[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head trauma, ruptured aneurysm and idiopathic CCF represent the main causes of direct CCF[ 1 ]. The incidence of iatrogenic CCF in interventional radiology is approximately 0.8%; this includes its occurrence as a complication during neurointerventional procedures, including coil embolization of aneurysms and intracranial percutaneous transluminal angioplasty and rarely after mechanical thrombectomy (MT)[ 3 ]. The risk factors for iatrogenic CCF include advanced age, internal carotid artery (ICA) tortuosity, changes in the atherosclerotic vessel wall, cavernous aneurysms as well as vessel wall fragility due to underlying connective tissue weakening ( e.g.…”
Section: Introductionmentioning
confidence: 99%